Nothing but the truth : a documentary novel - Avi, 1937- (New York : Orchard, 1991)
A ninth-grader's suspension for singing "The Star-Spangled Banner" during homeroom becomes a national news story.
"A Richard Jackson book."
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Newbery Medal/Honor
6.9
7-10
Keywords: High schools -- Fiction; Schools -- Fiction; High schools -- Fiction; School stories